'Remote parenting': parents' perspectives on, and experiences of, home and preschool collaboration. Issue 2 (4th March 2018) - Vuorinen, Tuula
ABSTRACT: This article explores parents' perspectives on, and experiences of, home and preschool collaboration. The data consist of in-depth interviews with 10 parents with one or several children attending preschool. The research process of gathering and analyzing data follows the procedures of constructivist grounded theory. The results show how parents seek to practice 'remote parenting' in order to shoulder their parental responsibilities for their child's well-being and care while they are away from their child. Parents approach situations they find difficult at preschool in different ways, including staying in the preschool and appreciating the collaboration with practitioners, working for change, coping with the situation, or changing preschools. Parents' experiences of home and preschool collaboration differ in significant ways, and there is, therefore, a need to visualize and discuss norms and values that shape the conditions for parental collaboration. The results might be useful for stakeholders and policy-makers on different levels.